2006
DOI: 10.3727/000000006783991818
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profile of B16(F10) Murine Melanoma Cells Exposed to Hypoxic Conditions In Vitro

Abstract: Hypoxia is an important feature of tumor microenvironment, exerting far-reaching effects on cells and contributing to cancer progression. Previous studies have established substantial differences in hypoxia response between various cell lines. Investigating this phenomenon in melanoma cells contributes to a better understanding of cell lineage-specific hypoxia response and could point out novel hypoxia-regulated genes. We investigated transcriptional activity of B 16(F10) murine melanoma cells cultured for 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 48 publications
(15 reference statements)
2
31
0
1
Order By: Relevance
“…These data revealed that the overexpression of hnRNP-K promoted metastasis by induction of signaling cascades involved in extracellular matrix, cell adhesion, invasion, and angiogenesis. Tmsb4x, an actin monomer-binding protein involved in cell migration and angiogenesis, was shown to be associated with tumor development (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…These data revealed that the overexpression of hnRNP-K promoted metastasis by induction of signaling cascades involved in extracellular matrix, cell adhesion, invasion, and angiogenesis. Tmsb4x, an actin monomer-binding protein involved in cell migration and angiogenesis, was shown to be associated with tumor development (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the promoter region of chimeric type galectin-3 gene contains binding sites for the transcription factor HIF-1, which drives hypoxia-induced galectin-3 mRNA and protein expression, as observed in HeLa cells and mouse embryonic fibroblasts from HIF-1a wild-type, but not HIF-1a null mice [90]. The expression of galectin-3 gene was also strongly upregulated by hypoxia in the murine melanoma cell line BF-F10 [91]; however, this effect could be cell-specific because subsequent studies revealed no significant changes in five out of six human melanoma cell lines [92]. It is interesting to note that the combined hypoxia-induced upregulation of galectin-3 and epidermal growth factor receptor has been proposed to enhance the invasive potential of tumor cells that are exposed to stressed microenvironmental conditions [93].…”
Section: Chimeric Type Galectin-3mentioning
confidence: 95%
“…Bhlhb2 is induced by hypoxia and represses MITF expression Transcription factors Bhlhb2, Sap30, Atf3 and Mxi1 were reported to be regulated upon exposure of B16 melanoma cells to hypoxic conditions (Olbryt et al, 2006). Therefore, we examined the effect of cobalt or hypoxia on these transcription factors.…”
Section: Mitf Regulates Mesenchymal Phenotype and Invasiveness In Hummentioning
confidence: 99%